Battling without Beards: Synesius of Cyrene’s Calvitii encomium, Arrian’s Anabasis Alexandri and the Alexander discourse of the fourth century AD - Christian Djurslev (Universitat Autònoma de Barcelona. Departament de Ciències de l’Antiguitat i l’Edat Mitjana., 2018)
This paper explores the literary tradition of the curious chreia that Alexander ordered his men to shave off their beards before battle. The story is represented by various sources from the imperial period but most prominently in the Encomium of Baldness by Synesius of Cyrene. The latter source posits that the story comes from the History of Alexander by Ptolemy, son of Lagus, but this claim cannot be true when Synesius’ version is compared to other extant uses of the chreia. This paper exemplifies some of Synesius’ methods of working, arguing that we need to invest more energy in appreciating the wider tradition of Alexander in late antiquity to understand our earlier texts.